Fluorescence microscopy studies of molecular diffusion and interaction within self-assembled nanomaterials - Xu, Hao (Kansas State University, 2016)
This dissertation describes the application of fluorescence microscopy techniques to investigations of mass transport phenomena in self-assembled nanomaterials. The microscopic morphologies of the materials and the mass-transport dynamics of probe molecules dispersed within them were assessed with high temporal and spatial resolution by single molecule imaging and spectroscopic methods. Three distinct sets of experiments were performed in completing the work for this dissertation. In the first study, single molecule imaging was employed to explore the interactions and field-induced migration of double-stranded DNA (ds-DNA) molecules with nanostructured Pluronic F127 gels. While DNA interactions with nanostructured gels have been explored in the past, none had apparently looked at these interactions in gels comprising hexagonally ordered arrays of cylindrical micelles. Therefore, these studies focused on materials DNA dispersed in flow aligned hexagonal F127. DNA molecules were found to be strongly confined in the hexagonal mesophase structures from their elongation, alignment, and exclusively occurred electrophoretic migration in the direction parallel to the cylinder long axis. These observations will lead to a better understanding of macromolecular interactions with nanostructured gels like those now being investigated for use in drug delivery and chemical separations. In the second study, imaging-fluorescence correlation spectroscopy (imaging-FCS) was used to study the rate and mechanism of sulforhodamine B (SRB) dye within novel bolaamphiphile-based self-assembled nanotubes. These nanotubes were only recently developed and their mass transport properties remain largely unexplored. The nanotubes employed here are unique because they incorporate amine groups and glucose groups on their inner and outer surfaces, respectively. Wide-field fluorescence video microscopy was first applied to locate and image dye-doped nanotubes dispersed on a glass surface. Imaging-FCS was employed as it allows for the dynamics to be recorded simultaneously from a large sample region, thus the SRB mass transport within nanotubes can be spatially resolved. The coulombic interactions between cationic ammonium ions on the inner nanotube surface and the anionic SRB molecules was shown to play a critical role in governing dye dynamics under varied pH and ionic strength conditions. Mass transport of SRB within the nanotubes is concluded to occur by a desorption-mediated Fickian diffusion mechanism. In the third set of experiments, solvatochromic dye molecules were employed in novel imaging-FCS studies of the role played by partitioning in governing mass transport phenomena within the same organic nanotubes used above. Two forms of the solvatochromic dye Nile Red (NR) were employed: the commercial hydrophobic form of NR, and a more polar derivative 2-hydroxybenzophenoxazinone (named NR-OH). The partitioning of dye molecules within the nanotubes was investigated assessing the diffusion rate for each dye. The preliminary results suggested NR and NR-OH preferentially partitioned into the tube walls and the ethanol phase filling the tubes, respectively. The diffusion coefficient data indicated NR-OH diffused faster than NR, consistent with the presence of NR-OH in a relatively less viscous environment (e.g., the ethanol phase filling the tubes). The results of these studies afford information essential to the use of organic nanotubes in controlled drug release and possibly in catalysis applications.
Keywords: Fluorescence microscopy; Molecular diffusion; Self-assembly; Nanomaterials